2015
DOI: 10.1002/pssc.201510096
|View full text |Cite
|
Sign up to set email alerts
|

Static response and stiction analysis of MEMS micromembranes for optical applications

Abstract: The scope of this paper is to investigate the designing, manufacturing and testing of MEMS micromembranes with high mobility. The implementation field of micromembranes is in the optical applications. The mobility of MEMS membranes is provided by the geometry of hinges and their reliability depends on geometrical dimensions and the material behavior. Deformation in different planes of a micromembrane gives the rise to the occurrence of complex efforts that can reduce the operation time especially if one takes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In [20] is suggested that single asperity contact occurs when the adhesive force acting on the asperity deforms it by at least the RMS roughness. Then, using the model proposed by the authors in [19] the results were extrapolated to the entire length of contact between AFM tip and samples. In interpreting the data presented in the ambient temperature at different values of relative humidity it was necessary to assume a value for Kelvin radius as 0.4 nm and to establish the equilibrium separation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [20] is suggested that single asperity contact occurs when the adhesive force acting on the asperity deforms it by at least the RMS roughness. Then, using the model proposed by the authors in [19] the results were extrapolated to the entire length of contact between AFM tip and samples. In interpreting the data presented in the ambient temperature at different values of relative humidity it was necessary to assume a value for Kelvin radius as 0.4 nm and to establish the equilibrium separation.…”
Section: Discussionmentioning
confidence: 99%
“…Studying the contact line segment, it was established that there were 15 contact points which were modelled as the contact between the sphere and a plane due to the roughness of SU-8 and AFM tip. Then the total adhesion was computed according to [19] and the results are presented in Fig. 5.…”
Section: Analytical Interpretation Of Adhesion Forcementioning
confidence: 99%
“…The thermal gradient deforms the micromirror based on thermal dilatation of structure. Moreover, the modulus of elasticity decreases under the thermal relaxation effect of material with influence on the mechanical response of system [4]. The mechanical response of system depends on the out-of-the plane stiffness that is directly proportional with the modulus of elasticity of material.…”
Section: Temperature Effect On the Optical Mems Component Responsementioning
confidence: 99%
“…A thermal gradient introduces softening due to Young's modulus -temperature relation and a thermal relaxation, which changes the rigidity of material [4,5]. The lifetime of optical MEMS devices can also be influenced by temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Stiction is one of the most important and unavoidable failure problems of micromembranes under large deflection. Stiction is the adhesion of contacting surfaces due to surface forces (van der Waals, capillary forces, Casmir forces, hydrogen bridging, and electrostatic forces) [6]. The restorative force (pull-off force) of a micromembrane from substrate, opposite to the adhesion force, depends on the micromembrane stiffness.…”
Section: Introductionmentioning
confidence: 99%